BERHIAS MENCIPTAKAN LINGKUNGAN SEKOLAH SEHAT - ., Suharti (Jurnal Pembelajaran Prospektif, 2021)
Creating a healthy school environment is the most important thing that must be prepared by the education unit. A healthy school environment can be used as a fun learning resource for the achievement of optimal learning processes and outcomes. This Best Practice aims to determine the steps taken in an effort to create a healthy school environment. The location of the study was carried out at SMP Negeri 3 Jawai Selatan. In an effort to create a healthy school environment, the authors took activity steps called the BERHIAS Movement. BERHIAS is an acronym for Clean, Green, Beautiful, Beautiful, and Healthy. This movement is carried out regularly in schools so as to create a healthy school environment and is proven by satisfactory achievements with the title of Second Runner Up in the Healthy School Competition held by the local government of Sambas Regency in 2019